2022
DOI: 10.1002/adfm.202208404
|View full text |Cite
|
Sign up to set email alerts
|

Integrin‐Enriched Membrane Nanocarrier for the Specific Delivery of RGD‐modified Relaxin Analog to Inhibit Pancreatic Cancer Liver Metastasis through Reversing Hepatic Stellate Cell Activation

Abstract: Liver metastasis is common in patients with pancreatic cancer (PC) and is the leading cause of death associated with PC. Liver fibrosis induced by activated hepatic stellate cells (HSCs) creates a favorable metastatic microenvironment that promotes metastasis growth. B7-33, a therapeutic peptide (relaxin analog) that targets relaxin family peptide receptors on activated HSCs, inhibits the pSMAD2/3 signaling pathway and weakens the fibrogenic properties of activated HSCs. However, the short half-life and highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Many researchers found that bile secretion was related to fibrosis disease [ 44 ]. Zhang et al found that B7-33 which targets relaxin family peptide receptors can activate hepatic stellate cells (HSCs) can weaken the fibrogenic properties of activated HSCs [ 45 ]. Adrenergic signaling has been implicated in cancer initiation, progression [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers found that bile secretion was related to fibrosis disease [ 44 ]. Zhang et al found that B7-33 which targets relaxin family peptide receptors can activate hepatic stellate cells (HSCs) can weaken the fibrogenic properties of activated HSCs [ 45 ]. Adrenergic signaling has been implicated in cancer initiation, progression [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these issues, Zhang et al added the cRGD sequence to the end of the B7-33 (forming RGD-B7-33), which did not affect the anti-fibrosis efficacy of B7-33. 44 With the cRGD sequence, the RGD-B7-33 could be loaded onto the human umbilical vein endothelial cell (HUVEC) cell membrane derived nano-carriers through the specific interactions of cRGD with integrins (overexpressed on the HUVEC membrane) (Fig. 3A).…”
Section: Drug Carrier Design Inspired By Specific Molecular Interacti...mentioning
confidence: 99%
“…In another case, peptide drugs with inherent targeting properties should not be encapsulated in the carriers, but conjugating them to the surface of carriers may reduce their targeting activity and efficacy. 44–46 Besides, nucleic acid drugs may detach from the carriers during transportation in the body since the electrostatic adsorption is not stable in the complicated physiological environment. 47,48 Therefore, new carriers and/or loading strategies need to be developed to achieve effective loading of these mentioned drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Fueled by the advances in biotechnology and materials science, nanotechnologies have been widely investigated for cancer treatment, aiming to enhance safety, accuracy, and efficacy by leveraging the unique properties of engineered nanomaterials 20 , 21 . These materials are usually designed in the form of nano- and/or microparticles to alter the biodistribution and pharmacokinetics of the therapeutic agents they are linked with, or to serve as drug reservoirs, or both 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%